A lei do valor como limite ao desenvolvimento da economia brasileira - Galípolo, Gabriel Muricca (2008)
The concentration of income and social inequality are the characteristics that, despite the economic growth played throughout the twentieth century, still make Brazil a country underdeveloped. Historically the insertion of the Brazilian economy in the international division of labour, presented opportunities for external financing that limit the development: trade surpluses, especially on the export of agricultural products, which impact negatively on productivity of wages-goods and aggravate the concentration of income; or debt that end up raising the need for international currencies in the long term, supporting the vice of origin. These relations do not stem from the lack of capitalist development, rather the contrary, respond fully to the attention of the law of value. His reversal and overrun, therefore, can not result from private and individual decisions, but of the mediation of the state in organizing the production process, stimulating it in favour of social needs